Interaction between Ni/Ti nanomultilayers and bulk Ti-6Al-4V during heat treatment - Cavaleiro, André João (2018)
The diffusion bonding of Ti-6Al-4V to NiTi alloys assisted by Ni/Ti reactive multilayer thin films indicates the diffusion of Ni from the filler material towards bulk Ti-6Al-4V. As a consequence, the fragile NiTi2 intermetallic phase is formed at the joint interface. In this context, the aim of this work is to investigate the occurrence of Ni diffusion from Ni/Ti nanomultilayers towards Ti-6Al-4V substrates. For this purpose, multilayer coated Ti alloys were studied in situ at increasing temperatures using synchrotron radiation. After heat treatment, scanning electron microscopy (SEM) analyses were carried out and elemental map distributions were acquired by electron probe microanalysis (EPMA). The EPMA maps confirm the occurrence of Ni diffusion; the presence of Ni in the substrate regions immediately underneath the nanomultilayers is clearly indicated and becomes more pronounced as the temperature increases. The presence of Ni is observed in the same locations where V is found, thus in β-Ti grains of Ti-6Al-4V. At the same time, the synchrotron results together with SEM analyses allow the increase of the amount of β-Ti phase in Ti-6Al-4V to be identified, while the thin films are mainly constituted by NiTi2. Therefore, the presence of the brittle NiTi2 intermetallic phase can be avoided if Ni diffusion is prevented.